The Curse of the Tablas Strait: An Interrogation of Maritime Accidents from 1902-2008 - Poblador, Karl Friedrik K. (BANWAAN: The Philippine Journal of Folklore, 2025)
When the M.T. Princess Empress sank off the northeast coast of Mindoro  in the early morning of February 28, 2023, she became yet another addition to the list of vessels that have met their fate along the treacherous  Tablas Strait. The unusually large number of disasters that have taken place in that vicinity, including one of the worst maritime tragedies in history, has created a contemporary narrative about the existence of the so-called "Romblon Triangle," which has become the watery grave of thousands of souls since the beginning of the twentieth century. While the death toll from the sinkings and collisions that have taken place in that area is irrefutable, there are logical explanations that could dispel the  myth about the Tablas Strait being cursed. Hence, this article revisits official accounts of tragic events that took place in that waterway to provide analysis that could dispel the myth about the Tablas Strait being cursed. Regardless, no amount of fact-based historical accounts or even scientific analysis may be enough to dispel the mysteries and lore about this waterway, which is among the most heavily traversed in the archipelago. Keywords: interisland shipping, maritime disasters, Tablas Strait, Dona Paz, Romblon Triangle